The Role of Leadership In Improving Employee Discipline - Astry Conny Simorangkir; Betty A. S. Pakpahan; Sandy Ariawan (Jurnal Christian Humaniora, 2021)
Discipline is very important because discipline plays a role in creating disciplined and productive employees. Discipline means carrying out its responsibilities in accordance with office regulations, thus employees will become more productive and able to work effectively and efficiently. One of the factors that affect the discipline of work is the example of the leader, the example of the leader is very instrumental in determining the discipline of employees, because the leadership is used as an example and role model by his subordinates. The purpose of this study was to analyze the influence of leadership on work discipline. This research was included in associative-quantitative research, which was research that connects two or more variables to see the influence between variables through hypothesis testing. In this study, researcher gave five alternative answers to respondents using a scale of one to five. The population in this study was employees at the Office of Cooperatives, Small and Medium Enterprises, Industry and Trade of North Tapanulli Regency as many as 30 people under the leadership of echelon 3. The R Square value of 0.744 means that 7.44% of employee work disciplinary variables (Y) can be explained by leadership (X). While the remaining 25.6% can be explained by other variables that were not studied in this study. Based on the results of the analysis of this study where the leadership plays a role in the discipline of employees' work, this is because good leadership is one of the important factors in the process of disciplining employees' work. Leadership can affect employee discipline and result in the form of work requirements that employees will carry out. If the leadership in the company or organization is good and has the ability to influence or control its employees in carrying out office tasks then the work discipline will be improved as expected by the company.